Analisis Pendidikan Karakter Kedisiplinan Siswa Melalui Pembiasaan di Kelas V SDN Barusari 02 Semarang - Ayu Tri Ambarwati; Fine Reffiane; Mudzanatun Mudzanatun (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of this study was to describe the implementation of disciplinary character education for students through morning habits at SDN Barusari 02 Semarang, in class V, which consisted of 26 students. This research uses descriptive qualitative method. The research subjects were teachers and students V. Data collection techniques used data triangulation, namely observation, interviews and documentation. The results showed that the discipline character education of students through morning habituation in class V SDN Barusari 02 Semarang was well implemented. This activity is carried out with the existence of ceremonial disciplinary activities, morning gymnastics. All these activities are carried out by the school through the habituation method. Students have carried out morning habituation activities well without being accompanied by the teacher. Based on the results of this study, it can be concluded that the success of disciplinary character education activities can be through morning habituation activities before starting morning lessons.